2022
DOI: 10.3389/fped.2021.797684
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Widefield Optical Coherence Tomography in the Diagnosis of Retinopathy of Prematurity

Abstract: Recent advances in portable optical coherence tomography (OCT) and OCT angiography (OCTA) have resulted in wider fields of view (FOV) and shorter capture times, further expanding the potential clinical role of OCT technology in the diagnosis and management of retinopathy of prematurity (ROP). Using a prototype, handheld OCT device, retinal imaging was obtained in non-sedated infants in the neonatal intensive care unit (NICU) as well as sedated infants in the operating room of Oregon Health & Science Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Previous work using an artificial intelligence–based vascular severity score compared with clinical diagnosis has suggested that changes in vascular severity (dilation and tortuosity) are associated with changes in the stage and/or extent of disease. Using OCT to visualize the retinal periphery, it is possible to observe clinical progression of so-called popcorn retinal neovascularization, which occurs posterior to the ridge, as well as the coalescing into the typical stage 3 lesion, the development of retinoschisis and tractional retinal detachment, and the relationship between those features and vascular severity in the posterior retina . In addition, OCT may be useful for monitoring and characterizing patterns of disease regression following both spontaneous resolution of disease and treatment-induced disease regression …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work using an artificial intelligence–based vascular severity score compared with clinical diagnosis has suggested that changes in vascular severity (dilation and tortuosity) are associated with changes in the stage and/or extent of disease. Using OCT to visualize the retinal periphery, it is possible to observe clinical progression of so-called popcorn retinal neovascularization, which occurs posterior to the ridge, as well as the coalescing into the typical stage 3 lesion, the development of retinoschisis and tractional retinal detachment, and the relationship between those features and vascular severity in the posterior retina . In addition, OCT may be useful for monitoring and characterizing patterns of disease regression following both spontaneous resolution of disease and treatment-induced disease regression …”
Section: Discussionmentioning
confidence: 99%
“…However, recent advances in swept-source handheld OCT devices have been promising . Previous work has provided qualitative evidence that OCT B-scans reveal progressive changes in the retinal topography associated with increasing disease stage …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the early work using OCT work has focused on macular manifestations of ROP, such as the presence of macular edema, vitreous opacities, and the presence of retinoschisis posterior to the ridge ( 3 , 4 , 30 ). Widefield OCT has demonstrated the potential to provide real-time en face visualization, objective assessment of the peripheral stage, longitudinal monitoring of disease progression and regression, and detection of early vitreoretinal interface abnormalities ( 13 , 14 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 105° FOV system has potential to provide objective diagnosis in pediatric retinal diseases with predominantly extramacular pathology, like ROP, and contribute to new insight in these disease processes. We recently described our experience using these devices for ROP screening in the neonatal intensive care unit (NICU) in awake infants ( 13 , 14 ). Here, we present a review of the potential clinical benefits and applications of widefield (WF) and ultra-widefield (UWF) handheld OCT in pediatric retina patients undergoing examinations under anesthesia (EUA) for a variety of conditions.…”
Section: Introductionmentioning
confidence: 99%